Cas d’absence d’article en français : difficultés des apprenants et proposition d’une analyse unifiée - Lebas-Fraczak, Lidia (Studia Romanica Posnaniensia, 2011)
Given the difficulties encountered by learners of French in deciding whether in a noun phrase an article is to be used or not, we consider that it is necessary for them to apprehend the general function of the determiner in opposition to the cases of the absence of determiner in a nominal expression. Having noted that the usual explanations of these cases, which are based on semantic and grammatical criteria, are insufficient, we put forward an analysis based on a pragmatic-and-discursive factor: the communicative status of a noun within an utterance. We thus consider that the determiner serves to place a noun in the center of attention whereas the absence of determiner marks a defocalized status of a noun.